(3GdeLGdS hGdeSGjQGJs - (3GdbGVj GdfYeGf Hf Mjhf , CHh Mfjag GdfYeGf Hf eMeO Hf efUhQ Hf CMeO Hf Mjhf GdeUQj,J (B363 (3g` s ((3BOe Hf eMeO Ydi GdcLQGJi GdShQJi s)
(3ChdgG (B:s
(3bGd GdbGVi GdfYeGf Hf eMeO (B: (3SeYJ GdEeGe GdeYR dOjf Gddg UdhGJ Gddg Ydjg jhekG hbO bQH YjO GdCVMi , hSCd Yf eLF cJGeI ef GdCYeGd dTghQ GdYjO , abjd dg (B: (3ge jG CejQ GdeDefjf jJSGQHhf , hbO ZU GdbUQ Hge s
(3BNQgG (B:s
(3hcGf jhe SQhQ NJe CjGe GdWghQ GdJi bOefG PcQ GdSQhQ ajgG , heG Yde GdfGS ef aVd hdi Gddg HgG , UdhGJ Gddg Ydjg hYdi GdCFeI GdWGgQjf ef Sdag , hGdUahI GdegOjjf ef Ndag hSde cKjQkG s
(3GdbSe GdKGfis
(3fbdJ GdfSNI ef fSNI cJHgG eMeO Ydi Hf edG SdWGf Ydi ai HdO HQgGfjhQs
(3hCJe cJGHJgG ai GdJGSY hGdYTQjf ef UaQ SfI (B1332 (3g`s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdCOHs